STANDARISASI PARAMETER SPESIFIK EKSTRAK UMBI BAWANG DAYAK (Eleutherine Americana Merr.) - Anggraini Toar; Herny E.I. Simbala; Gerald Rundengan (Sam Ratulangi University, 2023)
ABSTRACT ANGGRAINI N. TOAR Standardization of Specific Parameters of Dayak Onion Tubers Extract (Eleutherin americana Merr.) Under the guidance of HERNY E. I. SIMBALA as chairman and GERALD RUNDENGAN as member. Dayak onion bulbs (Eleutherine americana Merr.) belonging to the Iridaceae family, have been used by the Dayak community for generations as medicinal plants for various types of diseases such as breast and colon cancer, hypertension, diabetes mellitus, hypercholesterolemia and stroke. This study aims to determine the results of the standardization of specific parameter tests. The results of this study indicate that the extract produced is a thick extract, brownish red in color, has a bitter taste, and has a distinctive smell. The content of compounds dissolved in water is 26.388%, while the levels of compounds dissolved in ethanol are 4.522%. Contains secondary metabolites in the form of alkaloids, flavonoids, saponins, quinones, steroids and triterpenoids. Total flavonoid content of 1.2%. Keywords: Standardization, Eleutherin Americana Merr,Specific Parameters